A hospital based cross-sectional study on platelet parameters in adult patients with dengue, its serological subgroups, and controls. (17th February 2022) - Shahila M, Antony Gnana; Jothilingam, Prabhavati
Abstract: Our objective was to analyze if there was a significant relationship between platelet parameters (PLT, MPV, PDW, P-LCR, PCT) among dengue, its serological subgroups and controls. Serologically proven adult patients with dengue {(n = 238) (NS1 positive = 218, IgM positive = 14, NS1 & IgM positive = 6)} and age- and gender-matched controls (n = 254) were included. The MPV, PDW and P-LCR were significantly higher, and PLT and PCT were significantly lower in cases compared with controls. Cases as well as controls showed a positive correlation between PLT and PCT, both parameters individually showed negative correlation with MPV, PDW, P-LCR. MPV, PDW and P-LCR showed positive correlation with each other. The results were similar in the serological subgroups. Comparison of our results with other studies points toward an overall hyperdestructive etiology for thrombocytopenia in dengue. There were two subgroups of cases based on the severity of thrombocytopenia. The mean/median value of all the platelet parameters was lesser in the ≤20k group than the >20k group, except for PDW, which was high although not statistically significant. Suppression of megakaryopoiesis with concomitant immune destruction of platelets in severe dengue could explain low MPV and P-LCR with a high PDW in view of the presence of microthrombocytes as a result of immune destruction. Although an overall hyperdestructive mechanism contributes to thrombocytopenia in dengue, regular monitoring of the platelet indices could reflect the status of megakaryopoiesis and thrombokinetic axis, thus aiding easy determination of pathophysiology and treatment.